Mobile Virtual Laboratory as Innovative Strategy to Improve Learners’ Achievement, Attitudes, and Learning Environment in Teaching Chemistry - Samosa, Resty C. (Future Science / FSH-PH Publications, 2021)
As our world becomes more technologically advanced, research suggests that technology-rich learning environments support students as well. Mobile Virtual Laboratories can be used to replicate physical laboratories and augment the incorporation of technology inside science classrooms in an attempt to provide students with laboratory experiences that would not otherwise be available in high school settings. This study measured the effectiveness of mobile virtual laboratory as innovative strategy to improve learners’ achievement, attitudes, and learning environment in teaching chemistry. The study utilized one-group pretest–posttest design. The innovative strategy is calculated using this design by measuring the difference between the pretest and posttest scores, attitudes and learning environment in teaching chemistry. The study revealed that the utilization of the innovative strategy mobile virtual laboratory in teaching chemistry showed that learners have a strong positive attitude. More so, the learners have a strong positive learning environment when exposed to the innovative strategy mobile virtual laboratory based on the six domain of learning environment in teaching chemistry. As shown by the significantly higher mean in the posttest than in the pretest, the innovative strategy mobile virtual laboratory had a positive impact on the learners' achievement. Consequently, the learners exposed to the mobile virtual laboratory in teaching chemistry are significantly differ in pretest and posttest results. The findings of this study have the potential to reassure educational professionals, contribute to the body of research within the field of chemistry achievement, attitudes, and learning environment, and encourage further research into the efficacy of mobile virtual laboratories as a teaching tool.